New-Enrolled English Students’ Effort in Improving Their Speaking Skills: New Enrolled English Student's Efforts in Improving Their Speaking Skills - Nur magfirah; Aisyah At-Thahirah Rukh Umaera; Ardiana (Universitas Negeri Medan, 2025)
This study aims to identify effective strategies used by first-year students to enhance their speaking skills. Additionally, it seeks to explore how these students develop their speaking abilities and the factors that support their learning process. A qualitative approach was employed, with data collected through direct interviews. The study involved 10 first-year students majoring in English Education at Muhammadiyah University of Makassar. The findings reveal that students utilize a combination of speaking practice, watching movies, listening to music, interacting with native speakers, and leveraging technology or language-learning applications to improve their speaking proficiency. These findings emphasize the importance of varied learning strategies and external support in language acquisition, offering valuable insights for educators and language learners aiming to develop effective oral communication skills.